Designing chiral amido-oxazolines as new chelating ligands devoted to direct Cu-catalyzed oxidation of allylic CH bonds in cyclic olefins. Issue 7 (15th February 2019) - Samadi, Saadi; Jadidi, Khosrow; Samadi, Mojgan; Ashouri, Akram; Notash, Behrouz
Abstract: A new type of amido-oxazoline ligands was conveniently synthesized from inexpensive and commercially available materials in high yields and enantiomeric excesses. The corresponding chiral copper complexes with this class of ligands [C2 symmetric S, S -bis(amido-oxazoline-Cu(II) complex] were synthesized accordingly. The ORTEP diagram of ligand6a and complex6a -copper were compared and characterization of the complex confirmed the involvement of both dentate parts of the ligands, the oxygen and nitrogen atoms, in complexation with copper. The utilization of this amido-oxazoline ligands in the copper-catalyzed enantioselective esterification of allylic CH bonds of cyclic olefins with tert -butyl-4-nitrobenzoperoxoate resulted in the highest activities, yields (up to 95%) and enantioselectivities (up to 96%) in the presence of HZSM-5 zeolite. These new findings highlight the protocol as one of the most attractive and useful methods for the oxidation of the asymmetric allylic CH bond of cycloalkenes compared to other methodologies reported in the literature. Graphical abstract: